(untitled) (Prostor, 2024)
This study explores the relationship between users and the built environment through a post-occupancy evaluation (POE) conducted at the FNN Sustainability Centre, a noteworthy sustainable building in the region. The study involved a comprehensive approach, encompassing site visits, managerial interviews, and staff surveys. To establish a robust evaluation framework, a scale was developed by analyzing pertinent literature, and indicators were identified to gauge various aspects of the building’s performance. Throughout the scale development process, the SPSS data analysis program was used, and expert opinions were solicited to ensure a rigorous and comprehensive methodology. Evaluation categories included lighting, acoustics, climatic comfort and indoor air quality, use and comfort of systems, quality of space and perception, awareness of sustainability and productivity. The building emerged as a physically and psychologically conducive workplace that heightened employee awareness of sustainability. The study identified specific concerns, such as noise disturbance for open-office workers and glare-related issues, which serve as valuable feedback for potential adjustments.